Influence of the preparation method and the support on H2O 2electrogeneration using cerium oxide nanoparticles - Assumpcão, M. H M T; Moraes, A.; De Souza, R. F B; Calegaro, M. L.; Lanza, M. R V; Leite, E. R.; Cordeiro, M. A L; Hammer, Peter [UNESP]; Santos, Mirian Cristina dos [UNESP] (Elsevier, 2013)
This work describes the influence of the preparation method and the carbon support using a low contentof cerium oxide nanoparticles (CeO2/C 4%) on H2O2electrogeneration via the oxygen reduction reac-tion (ORR). For this purpose, the polymeric precursor (PPM) and sol-gel (SGM) methods with Vulcan XC72R (V) and Printex L6 (P) supports were employed. The materials were characterized by X-ray diffrac-tion (XRD), X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM). TheXRD analysis identified two phases comprising CeO2and CeO 2-x. The smallest mean crystallite size wasexhibited for the 4% CeO2/C PPM P material, which was estimated using the Debye-Scherrer equation tobe 6 nm and 4 nm for the CeO2and the CeO 2-xphases, respectively, and was determined by TEM to be5.9 nm. XPS analysis was utilized to compare the oxygen content of the 4% CeO2/C PPM P to Printex L6.The electrochemical analysis was accomplished using a rotating ring-disk electrode. The results showedthat the 4% CeO2/C specimen, prepared by PPM and supported on Printex L6, was the best electrocatalystfor H2O2production in 1 mol L -1NaOH. This material showed the highest ring current, producing 88%H2O2and transferring 2.2 electrons per O 2molecule via the ORR at the lowest onset potential. Addition-ally, the ring-current of the 4% CeO2/C PPM P material was higher than that of Vulcan XC 72R and PrintexL6, the reference materials for H2O 2production, indicating the highest electrocatalytic activity for the 4%CeO2/C PPM P material. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Cerium oxide nanoparticles; Electrogeneration of hydrogen peroxide; Oxygen reduction reaction; Cerium oxide nanoparticle; Electrocatalytic activity; Electrochemical analysis; Electrogeneration; Polymeric precursors; Reference material; Rotating ring-disk electrode; Electrolytic reduction; Nanoparticles; Oxides; Photoelectrons; Sol-gels; Transmission electron microscopy; X ray photoelectron spectroscopy; Materials